Synergy of Effectuation and Causation: An Emotional Complexity Perspective - Chen, Huangen; Xu, Qian (Frontiers in Psychology, 2022)
This paper enriches the literature on entrepreneurial decisions by investigating the antecedents to an entrepreneur’s synergetic use of causal and effectual logics. Based on entrepreneurial metacognition and emotional complexity theories, we argue that an entrepreneur’s emotional complexity, referred to as the granular experience of, or variety in, experienced emotions during the entrepreneurial task, would contribute to the synergetic use of decision logics. With the survey data gathered from 218 Chinese entrepreneurs, we find that entrepreneurs with higher emotional complexity would be more likely to adopt two types of entrepreneurial logics in tandem, and the cognitive flexibility mediates this positive relationship. This study thereby helps to unravel some of the complexities behind entrepreneurs’ choice of decision logics.